High TRIM44 expression as a valuable biomarker for diagnosis and prognosis in cervical cancer. Issue 3 (6th March 2019) - Liu, Shuang; Meng, Fanling; Ding, Jing; Ji, Hongying; Lin, Mu; Zhu, Jiaqi; Ma, Rong
Abstract : Tripartite motif containing 44 (TRIM44) has been reported to be up-regulated in multiple aggressive malignant tumors. However, its expression status and clinical significance in cervical cancer remain unknown. The purpose of this study was to investigate the clinical significance of TRIM44 expression and the prognosis in patients with cervical cancer (CC). Fresh frozen tissues from 5 samples of CC and 4 normal cervical tissues were analyzed for TRIM44 expression using RT- PCR and Western blot analysis. 122 paraffin-embedded surgical specimens from patients with CC were collected for an immunohistochemistry. TRIM44 expression was found to be significantly up-regulated in cervical cancer specimens compared with adjacent normal tissues ( P <0.001). Statistical analysis showed that TRIM44 expression was significantly correlated with the International Federation of Gynecology and Obstetrics (FIGO) stage, histological grade and lymph node metastasis, but not with age, histological type, and tumor size. Kaplan–Meier survival analysis suggested that high TRIM44 expression was associated with poor prognosis. Patients highly expressing TRIM44 have significantly shorter overall survival (OS) ( P =0.006) and disease-free survival (DFS) ( P =0.002). Furthermore, multivariate Cox analysis showed TRIM44 was an independent risk factor for poor prognosis. Our study demonstrated that TRIM44 expression contributes to the progression of cervical cancer, and could be used as a marker of clinical diagnosis and prognosis of patients with cervical cancer.